L’interprétation argumentative en contexte - Kohei Kida (Corela)
Within the framework of argumentative semantics, argumentative interpretation takes place using two methods, one of which consists in determining the terms of an "argumentative chaining”, an argumentative discourse used to represent the meaning of an utterance. The aim of this article is to show that in such an interpretation, the context, and in particular the cotext, of the utterance to be interpreted can be exploited in various ways, which leads to rethink the notion of context.